Edukasi pencegahan scabies sebagai upaya meningkatkan PHBS di SMA Zainul Hasan 1 Genggong - Umi Narsih; Luluk Latifah; Hasyim Kholili; Rizqiyah Amalia Fitroh (P3HKI - Universitas Muhammadiyah Parepare, 2025)
Scabies is a contagious skin disease caused by an infestation of the mite Sarcoptes scabiei. This condition spreads easily, particularly in densely populated environments such as Islamic boarding schools and residential schools, which often face limitations in hygiene and sanitation facilities. The primary symptom of scabies is intense itching, especially at night, which can interfere with comfort, sleep quality, and students' concentration in learning. In addition to its physical effects, scabies also causes psychosocial disturbances due to social stigma and decreased self-confidence. The lack of student knowledge about scabies and inadequate practice of Clean and Healthy Living Behavior (PHBS) exacerbates the situation. This Community Service Program (PKM) aimed to increase students’ knowledge and awareness regarding scabies prevention through structured health education. The activity was conducted at SMA Zainul Hasan 1 Genggong, involving 32 student participants. The implementation methods included interactive counseling, distribution of educational leaflets, and knowledge evaluation using pre-test and post-test instruments. The results showed a significant improvement in students’ understanding, with an increase of 34.4%—from 62.5% (categorized as very good) before the intervention to 96.9% after the intervention. These findings demonstrate the effectiveness of educational approaches in enhancing student awareness and knowledge regarding scabies prevention and the importance of applying PHBS in daily life. This activity is expected to serve as a promotive and preventive intervention model that can be sustainably implemented in other school environments to foster a healthy culture from an early age.